A progressive damage model introducing temperature field for bolted composite joint with preload. (10th June 2019) - Liu, Wushuai; Yu, Fen; He, Zhenpeng; Qing, Guanghui
Abstract: A three-dimensional progressive damage model is proposed to predict the failure of bolted composite joint under the combined effect of temperature and bolt preload. The model introduces a constitutive equation accounting for the thermal strain. Meanwhile, the temperature-induced modification of stiffness and strength parameters are involved in the stress analysis model, failure criterion and material degradation rules. Considering the highly nonlinear problem of the model, the ABAQUS/Explicit solver is used for numerical simulation. A user defined subroutine VUMAT was developed and embedded into a FEA package to perform the failure analysis of bolted composite joint. In order to study the combined effect of temperature and bolt preload, a series of failure analysis of bolted composite joint subjected to different temperature and bolt preload levels have been performed using the proposed progressive damage model. Results show that when the preload exceeds the critical value, the bearing strength and stiffness decrease faster and faster with the increment of the temperature.